SMART MONITORING IMPLEMENTATION IN PREVENTING CORRUPTION IN REGIONAL BUDGET MANAGEMENT: A LITERATURE REVIEW OF EAST KALIMANTAN - Aniza Dwi Amanda; Cilvy Putri Ihksani; Firre An Suprapto (Jurnal Administrasi Publik dan Kebijaka (JAPK), 2026)
The increasingly complex management of regional budgets requires oversight systems that are adaptive, transparent, and capable of detecting irregularities at an early stage. This study analyzes budget governance problems in East Kalimantan and formulates a smart monitoring model as a strategy for preventing corruption and budget misuse in local public financial management. The research employs a descriptive qualitative approach based on literature review and secondary document analysis, including regulations, official reports, and public policy news related to the East Kalimantan APBD for the 2025–2026 period. The findings identify three main weaknesses in the budget oversight system: the absence of real-time budget tracking, limited public access to detailed expenditure information, and an ineffective early-detection mechanism for identifying patterns of irregular spending. In response, this study proposes a three-layer smart monitoring model consisting of a real-time digital ledger for early detection, an open public dashboard to strengthen transparency and social accountability, and an AI-based analytical system to identify budget anomalies. The model is expected to strengthen corruption prevention by integrating technology, institutional control, and public participation.